1881 Wash. Sess. Laws 76, An Act to Confer a City Govt. on New Tacoma, ch. 6, § 34, pt. 15 - (:unkn) unknown (General Publisher, 1881)
Authorized New Tacoma to regulate transporting, storing, or selling gunpowder, giant powder, dynamite, nitroglycerine, or other combustibles without a license, as well as the carrying concealed deadly weapons, and the use of guns, pistols, firearms, firecrackers.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER